Emotional intelligence and perfectionism among gifted and non-identified students - Dilek Ozdogan; Savas Akgul (International Journal of Emotional Education, 2023)
The current study comparatively examines the emotional intelligence and perfectionism of gifted and non-identified students. A total of 857 students participated in the study. Data were collected through the Positive and Negative Perfectionism Scale, which measures students’ perfectionism levels and the Bar-On Emotional Quotient Inventory Youth Version EQ-i:YV, which measures students’ emotional intelligence. Our findings indicate that gifted students' scores in the intrapersonal and adaptability subdimensions of emotional intelligence and their overall scores in emotional intelligence are higher than those of non-identified students; while non-identified students’ average score of positive perfectionism is higher than that of the gifted students. Additionally, we found a negative correlation between positive impression and negative perfectionism in the non-identified group, while the correlation between these variables was positive amongst the gifted participants. Our findings may help design successful educational and guidance programmes for the gifted and their non-identified peers and in-service programmes for their teachers and counsellors.